2018
DOI: 10.1177/0960327118758382
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of an L-type calcium channel blocker, amlodipine, on paracetamol-induced hepatotoxicity in rats

Abstract: Paracetamol (P), one of the most popular and commonly used analgesic and antipyretic agents, causes hepatotoxicity in overdoses. Amlodipine (AML), an L-type calcium channel blocker, has been shown to have anti-inflammatory activity by reversing the effect of calcium in the inflammation pathogenesis. In this study, the hepatoprotective activity of AML on P-induced hepatotoxicity was evaluated. Thirty male albino Wistar rats were divided into five groups: (1) control, (2) 2 g/kg of P, (3) 2 g/kg of P + 5 mg/kg o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 54 publications
(85 reference statements)
0
6
0
Order By: Relevance
“…Previous studies reported a different mechanism by which amlodipine exhibits beneficial modulation in the context of paracetamol-induced liver inflammation in Wistar rats (PMID: 29441826; PMID: 27829805). 71 , 72 However, the lack of gut microbiota analysis in previous studies hinders comparability with our study. Notably, it has been observed that paracetamol can induce gut dysbiosis in murine models.…”
Section: Discussionmentioning
confidence: 78%
“…Previous studies reported a different mechanism by which amlodipine exhibits beneficial modulation in the context of paracetamol-induced liver inflammation in Wistar rats (PMID: 29441826; PMID: 27829805). 71 , 72 However, the lack of gut microbiota analysis in previous studies hinders comparability with our study. Notably, it has been observed that paracetamol can induce gut dysbiosis in murine models.…”
Section: Discussionmentioning
confidence: 78%
“…Other possible markers of liver damage are GSH depletion and oxidative stress (Kaya et al 2018). Fisetin has been shown to have direct antioxidant activity and can also directly increase intracellular levels of GSH (Murtaza et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In a model of paracetamol‐induced hepatotoxicity in rats, amlodipine reduced the mRNA expression of TNF‐α in the animals' serum. Also, by immunohistochemistry, a reduction was found in TNF‐α expression in the cytoplasm of hepatocytes [45]. Another study showed that nifedipine reduces TNF‐α and IL‐6 levels in the serum of animals in a chilblain model [46].…”
Section: Discussionmentioning
confidence: 99%